Post-Divorce Rights of Women and Children in Pekalongan City, Central Java: Challenges in Islamic Law Analysis - Syukrawati, Syukrawati; Sidqi, Imaro; Nisa, Siti Maymanatun; Zufriani, Zufriani; Witro, Doli (Al-Ahkam, 2024)
The rights of women and children after divorce are often neglected. The article examines the reality of children's and women's rights in Pekalongan City, Central Java, Indonesia, focusing on the causes of non-fulfillment and the legal consequences. Data from 10 court decisions from the Pekalongan City Religious Court revealed a gap between post-court decision reality and the fulfillment of these rights. The research found that the non-fulfillment of children's and women's rights after divorce in Pekalongan is due to a lack of public knowledge about post-divorce execution procedures and related rights. The difficulty of spouses in ensuring the fulfillment of these rights is also reflected in the lack of application of Islamic legal knowledge on the obligation to provide maintenance by husbands. The legal consequences are devastating, emphasizing the need for improvements in the legal system, increased public knowledge, and the application of Islamic legal principles.